Effect of Annealing Temperature on ZnO Properties for CO2 Reduction - Fitrilawati, Fitri; Junita, Tri Komala; Mori, Ersika; Rayhan, Abel; Hendrawan, Kayla Putri; Aprilia, Annisa; Faizal, Ferry (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2026)
Zinc Oxide (ZnO), is a widely researched material for Carbon Capture applications due to its large surface area and adequate band gap. In this study, ZnO was synthesized using the sol-gel method with various annealing conditions, namely without annealing and annealing at 150°C, 300°C, and 450°C. The annealing process is carried out under inert conditions using a flow of nitrogen gas (N₂) to study the possibility of the appearance of defects in the ZnO material related to the process. XRD measurements showed that the size of ZnO crystals increased and there was a more regular structure as the annealing temperature increased. FTIR measurement results show the intensity of vibrational peaks that tend to be narrowed and more defined. SEM measurement results show a more defined morphology with a more uniform and fine particle size in ZnO annealed at 300°C and 450°C, thus affecting the atomic composition. EDS results show that the percentage of atomic O in ZnO decreases, indicating the presence of oxygen vacancies. ZnO that has a large crystal size has a band gap value that tends to decrease (red shift) so that it can slow down the recombination process and can increase its photocatalytic activity. Cylic Voltammetry (CV) test results from with ZnO as electrode, showed that ZnO annealed at high temperatures caused an increase in current density and a more negative potential change